Mexican experience on the design of catastrophic satellital parametric livestock insurances: operational implementation - Paz Pellat, Fernando; Bolaños, Martín; Pascual Ramírez, Fermín; Escamilla, Jesús; Cuesta, Mario; Zuñiga, José Inés (REVISTA TERRA LATINOAMERICANA, 2018)
The operational implementation of schemes for climate risk management, primarily insurance products, is an option to mitigate the effects of climate change and make efficient use of financial resources at regional and country levels. In this study the operational experience in implementing parametric insurance products in Mexico, based on the conceptual-theoretical development of the implementation framework, is presented. Parametric design of livestock insurance satellite products is based on the relation Bm = kVI, where Bm is the total aerial biomass, VI is a spectral vegetation index and k is an empirical constant. To achieve this relationship, a linear relationship between the spectral index NDVIcp and the Bm, which becomes the index IVCP (1/NDVIcp) is used. The advantage of using the transformed 1/NDVIcp index is having linear patterns over time, which can be used for parameterization in operational terms. This development is discussed by using an algorithmic approach that considers the parameterization of vegetation growth curves, index 1/NDVIcp, for the AVHRR sensor. It also presents the operational experience of implementation in Mexico and validation campaigns are included. From operational experience, it is concluded that, in a complete cycle, even if the scheme developed reduces the basic risks associated with the use of short periods of insurance, the problem of growth cycle lags remains, constituting an inherent restriction when considering the beginning and end date of parametric insurance cover. Recommendations are given to improve the insurance products.